(untitled) (World Science, 2020)
Carrying out a technical examination of a cost estimate of a section of a highway is based on its certain technical and functional state. Different methods are used to establish the operational state. The expert method is the simplest, most affordable and, with strict adherence to the technique, provides high reliability. The essence of this method is the subjective consideration of situations from which one or more optimal ones should be selected.